Does objectively measured daily duration of forward bending predict development and aggravation of low-back pain? A prospective study - Julie Lagersted-Olsen; Birthe Lykke Thomsen; Andreas Holtermann; Karen Søgaard; Marie Birk Jørgensen (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: The aim of this paper was to investigate if objectively measured daily duration of forward bending of the trunk increases the risk of the development or aggravation of low-back pain (LBP) over one year in a working blue-collar population by examining (i) the incidence rate of LBP among workers reporting no LBP at baseline, and (ii) the aggravation of LBP among workers reporting LBP at baseline. METHODS: Using data from the Danish Physical Activity Cohort with Objective Measurements (DPhacto), the study measured forward bending of the trunk (>60˚) at work (FBW) and during leisure time (FBL), diurnally with accelerometers, and LBP with one-year monthly self-reports among 682 blue-collar workers from 15 workplaces. The development of LBP was investigated with Cox's proportional hazards model (N=200), and the aggravation of LBP was investigated with mixed model for repeated measurements (N=482). RESULTS: Workers with no LBP at baseline had a FBW median of 7.9 minutes/day. Workers with LBP at baseline had a FBW median of 7.3 minutes/day. No significant associations were found between daily duration of forward bending of the trunk and development or aggravation of LBP. Similar results were found in the secondary analyses, in which FBL, different degrees of forward bending (>30˚ and >90˚), and varying follow-up time since measurement were considered. CONCLUSION: Using objective measurements of forward bending and monthly follow-up of LBP over one year, this study did not confirm the hypothesis of a positive association between daily duration of forward bending and LBP.